(untitled) (Patan Prospective Journal, 2022)
During the monsoon of 2022, Kathmandu valley witnessed an unprecedented number of cholera cases in a brief period- on an epidemic scale. This event corresponded with a month-long stagnation of Municipal Solid Waste (MSW) in the streets of the valley after protests and blockades from the residents in Sisdole- the location of the only landfill serving the valley. This paper has entertained the correlation between the two entities and has scrutinized the idea. To add to the study, the trends re studied and evaluated. Observations and literature reviews suggest MSW making the situation of cholera worse if not causing it. This study has also provided suggestions for getting the situation better in the longer term using available literature and has laid the groundwork for further research regarding the relationship between the two to further understand their significance on one another.